1997
DOI: 10.1046/j.1365-2958.1997.4531718.x
|View full text |Cite
|
Sign up to set email alerts
|

The ssb‐113 allele suppresses the dnaQ49 mutator and alters DNA supercoiling in Escherichia coli

Abstract: SummaryMutations in the dnaQ gene, which encodes the proofreading ⑀-subunit of the DNA polymerase III holoenzyme, lead to a mutator phenotype caused by enhanced error rates during DNA replication. In this paper, we studied the influence of ssb mutations on the dnaQ49 mutator, because of the involvement of SSB protein in DNA replication. We found that the ssb-113 mutation suppresses the mutator phenotype of dnaQ49. The suppression effect resulted from an enhanced expression of the dnaQ49 allele as determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…SSB, possibly by virtue of its ability to stabilize the single-stranded regions in DNA, stimulates the enzyme activity. Support for this functional cooperation between topoisomerase I and SSB also comes from studies where an SSB allele is shown to influence DNA supercoiling levels in the cells (41). One would expect increased local concentration of both topoisomerase I and SSB at regions of DNA actively involved in replication process.…”
Section: Discussionmentioning
confidence: 92%
“…SSB, possibly by virtue of its ability to stabilize the single-stranded regions in DNA, stimulates the enzyme activity. Support for this functional cooperation between topoisomerase I and SSB also comes from studies where an SSB allele is shown to influence DNA supercoiling levels in the cells (41). One would expect increased local concentration of both topoisomerase I and SSB at regions of DNA actively involved in replication process.…”
Section: Discussionmentioning
confidence: 92%
“…This mechanism is based on the concept which was "rst proposed by Scheuermann and Echols (1984), and some evidence supporting it can be seen (e.g. Fujita et al, 1987;Foster & Marinus, 1992;Quinones & Neumann, 1997). In the DNA polymerase of Gram-positive bacteria, in contrast, both DNA synthesis and proofreading activities exist on a single polypeptide (Kornberg & Baker, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…26 The interaction between SSB and χ is critical as mutations within the protein interaction domain in SSB (e.g., ssb-113 ) are conditionally lethal. 27 Furthermore, strand displacement synthesis catalyzed by the Pol III HE in the absence of helicase is dependent on SSB. 28 SSB directly interacts with primase (DnaG) 29; 30 as well as with PriA.…”
Section: Introductionmentioning
confidence: 99%